Corporate Diversification and Firm Value in Financial Crisis in Vietnam - Kim Duc, Nguyen; Nhung, Nguyen Thi Hong; Nhu, Tran Vu Quynh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 33 No 4, 2017)
This research aims at assessing the relationship between corporate diversification and firm value ​​in the time of financial crisis in Vietnam. The research sample consists of 42 Vietnamese non-financial enterprises listed on HoSE from the first quarter of 2008 to the fourth quarter of 2011. We used two methods to estimate panel data regression: (1) Regression Method Pooled OLS and (2) Random Effect Model (REM). The results show that: (1) There is relationship between corporate diversification and firm value, however, corporate diversification should be implemented at either national or industrial level; (2) The financial crisis doesn’t dominanate this relationship and the implementation of diversification will contribute to improving the relative valuation of diversified firms in Vietnam regardless of financial crisis. This empirical result will help Vietnamese enterprises have a reference for considering and making decision related to corporate diversification. Keywords Diversification, firm value, financial crisis. References [1] Pindyck, R. S., Rubinfeld, D. L., Microeconomics, 8th edition, NewYork, Pearson, 2014. [2] Lewellen, W. G., “A pure financial rationale for the conglomerate merger”, The Journal of Finance, 26 (1971) 2, 521-537. [3] Berger, P. G., Ofek, E., “Diversification’s effect on firm value”, Journal of Financial Economics, 37 (1995), 39-65. [4] Volkov, N., Smith, G. C. C., “Corporate Diversification and Firm Value During Economic Downturns”, Quarterly Review of Economics and Finance, 55 (2015), 160-175. [5] Ansoff, H. I., “Strategies for Diversification”, Harvard Business Review, 35 (1957), 5, 112-124. [6] Chandler, A., “The Structure of American Industry in the Twentieth Century: A Historical Overview”, Business History Review, 43(1969) 3, 255-298. [7] Berry, C. H..,Corporate Growth and Diversification, Princeton NJ: Princeton University Press, 1975. [8] Andrews, K. R.,The Concept of Corporate Strategy, Homewood, IL: Richard D. Irwin, 1980. [9] Gluck, F. “A Fresh Look at Strategic Management”, The Journal of Business Strategy, 23 (1985). [10] Aaker, D. A.,Developing Business Strategies, 6th edition, NewYork, JohnWiley & Sons, 2001. [11] Rumelt, R. P., Strategy, structure, and economic performance, 1974. [12] Teece, D. J., “Economies of scope and the scope of the enterprise”, Journal of Econonomic Behavior and Organization, 1 (1980) 3, 223-247. [13] Jensen, M., and Meckling, W., “Theory of the Firm: Managerial Behavior, Agency Costs and Ownership Structure.”, Journal of Financial Economics, 3 (1976) 4. [14] Eisenhardt, K. M., “Agency theory:An assessment and review”, Academy of Management Review, 14 (1989) 1, 57-74. [15] Hoechle, D., Schmid, M., Walter, I., Yermack, D., “How much of the diversification discount can be explained by poor corporate governance?”, Journal of Financial Economics, 103 (2012) 1, 41-60. [16] Duchin, R., Sosyura, D, “Divisional managers and internal capital markets”, The Journal of Finance, 68 (2013) 2, 387-429. [17] Herzberg, F., Mausner, B., Snyderman, B.,The Motivation to Work, New York: John Wiley, 1959. [18] Etzioni, A.,A Comparative Analysis of Complex Organizations, New York: The Free Press, Revised and Enlarged Edition, 1975. [19] Donaldson, L., “A rational basis for criticisms of organizational economics: S reply to Barney”, Academy of Management Review, 15 (1990) 3, 394-401. [20] Donaldson, L., “The ethereal hand: Organizational economics and management theory”, Academy of Management Review, 15 (1990) 3, 369-381. [21] Barney, J. B., “The debate between traditional management theory and organizational economics: substantive differences or intergroup conflict?”, Academy of Management Review, 15 (1990) 3, 382-393. [22] Donaldson, L., Davis, J. H., “Stewardship Theory or Agency Theory: CEO Governance and Shareholder Returns”, Australian Journal of Management, 16 (1990) 1, 49-64. [23] Davis, J. H., Schoorman, F. D., Donaldson, L., “The Distinctiveness of Agency Theory and Stewardship Theory”, The Academy of Management Review, 22 (1997) 3, 611-613. [24] Matsusaka, J.G., Nanda, V., “Internal capital markets and corporate refocusing”, Journal of Financial Intermediation, 11 (2002) 2, 176-211. [25] Lins, K.V., Servaes, H., “Is corporate diversification beneficial in merging markets?”, Financial Management, 31 (2002) 2, 5-31. [26] Kuppuswamy, V., Villalonga, B., “Does diversification create value in the presence of external financing constraints? Evidence from the 2007-2009 financial crisis”, Working Paper, 2010. [27] Creal, D. D., Robinson, L. A., Rogers, J. L., Zechman, S. L. C., “The multinational advantage” (Workingpaper), 2012. [28] Lang, L. H. P., Stulz, R. M., “Tobin’s q, corporate diversification, and firm performance”, Journal of Political Economy, 102 (1994) 6, 1248-1280. [29] Servaes, H., “The value of diversification during the conglomerate merger wave”, The Journal of Finance, 51 (1996) 4, 1201-1225. [30] Denis, D. J., Denis, D. K., Yost, K., “Global diversification, industrial diversification, and firm value”, The Journal of Finance, 57 (2002) 5, 1951-1979. [31] Campa, J. M., Kedia, S., “Explaining the diversification discount”, The Journal of Finance, LVII (2002) 4, 1731-1762. [32] Palepu, K., “Diversi cation Strategy, Pro t Performance and the Entropy Measure”, Strategic Management Journal, 6 (1985), 239-255. [33] Santarelli, E. Tran, H.T., “Diversi cation Strategies and Firm Performance in Vietnam: Evidence from parametric and semi-parametric approaches”, Economics of Transition, 24 (2015) 1, 31-68. [34] Nguyễn Kim Đức, Huỳnh Kiều Tiên, Trần Bích Vân,“Thẩm định giá trị cộng hưởng - Lợi ích từ việc mua bán, sáp nhập doanh nghiệp tại Việt Nam hiện nay”, Tạp chí Công nghệ Ngân hàng, 118-119 (2016), 82-94.